Application of solar energy in Malaysian buildings: daylight performance of light pipes / Mulyadi Sibi - Sibi, Mulyadi (2005)
Daylighting is another significant renewable energy potential in Malaysia, being endowed with more than 10 hour of sunshine daily all year round. Its high level of global solar radiation ranging from 12 MJ/m2 /day to as high as 21 MJ/m2 /day had encouraged daylighting system applications and technologies for both commercial and non commercial use. Although Malaysia is still in the childhood stage of development in renewable energy, Malaysia has still got a wealth of renewable energy potential ready to be harnessed and utilized (Zain-Ahmed, 2000). Daylighting is relatively new renewable energy resource application in building. It can contribute to energy savings since it can supplement and replace electric lighting. In addition, daylighting can also be improve indoor air and visual quality This paper presents the performance of the system's optical component. A real model of light pipe and scale models of aluminum light pipes of different designs have been investigated experimentally under the sky conditions to identify the optimum design that is capable to capture, reflect and transmit daylight into the interior surface. The results of the scale modeling of the original system were compared with the actual system's performance under sky conditions.